Effects of Gamma Irradiation on Solid Propellant Conventional and UV-Cured Binders - Stefania Carlotti; Rocco Carcione; Beatrice D’Orsi; Tommaso Lusetti; Alessandro Finazzi; Jessica Scifo; Ilaria Di Sarcina; Matteo Ferrari; Alessia Cemmi; Filippo Maggi (Aerospace)
Ionizing radiations are responsible for bond scission, radical formation, and oxidative degradation of polymer matrices. This study focuses on the effects of gamma irradiation on solid propellant binders, targeting a comprehensive chemical and mechanical characterization of different formulations. Samples were produced either by conventional methods based on hydroxyl-terminated polybutadiene and standard polyaddition reaction using isocyanates, or innovative approaches involving UV-driven radical curing. The samples were irradiated for comparison and to study their evolution as a function of three absorbed doses (25, 45, 130 kGy) for preliminary characterization studies, using a 60-Co gamma source. Samples were irradiated in air at uncontrolled room temperature. The coupling of spectroscopy techniques (Fourier transform infrared—FTIR, Raman and electron paramagnetic resonance—EPR) and dynamic mechanical analysis (DMA) highlighted the key role of antioxidant agents in tailoring mechanical changes in the binder phase. The absence of antioxidants enhances radical formation, oxidation, and cross-linking. These processes lead to progressively increased rigidity and reduced flexibility as a function of the absorbed dose. Complex interactions between photocured components largely influence radical stabilization and material degradation. These findings provide valuable insights for designing novel radiation-resistant binders, enabling the development of solid propellants tailored for reliable, long-term permanence in space, and advancing the knowledge on the applicability of 3D-printed propellants.